Gellan gum microspheres crosslinked with trivalent ion: Effect of polymer and crosslinker concentrations on drug release and mucoadhesive properties - Boni, Fernanda Isadora [UNESP] (2016)
Gellan gum microspheres were obtained by ionotropic gelation technique, using the trivalent ion Al3+. The percentage of entrapment efficiency ranged from 48.76 to 87.52% and 22 randomized full factorial design demonstrated that both the increase of polymer concentration and the decrease of crosslinker concentration presented a positive effect in the amount of encapsulated drug. Microspheres size and circularity ranged from 700.17 to 938.32 ï¿½m and from 0.641 to 0.796 ï¿½m, respectively. The increase of polymer concentration (1-2%) and crosslinker concentration (3-5%) led to the enlargement of particle size and circularity. However, the association of increased crosslinker concentration and reduced polymer content made the particles more irregular. In vitro and ex vivo tests evidenced the high mucoadhesiveness of microspheres. The high liquid uptake ability of the microspheres was demonstrated and the pH variation did not affect this parameter. Drug release was pH dependent, with low release rates in acid pH (42.40% and 44.93%) and a burst effect in phosphate buffer pH (7.4). The Weibull model had the best correlation with the drug release data, demonstrating that the release process was driven by a complex mechanism involving the erosion and swelling of the matrix or by non-Fickian diffusion.